The dynamic role of sustainable development goals to eradicate the multidimensional poverty: evidence from emerging economy. Issue 3 (25th December 2023) - Cao, Yufei; Tabasam, Aftab Hussain; Ali, Syed Ahtsham; Ashiq, Anam; Ramos-Meza, Carlos Samuel; Jain, Vipin; Shabbir, Malik Shahzad
Abstract: This study empirically investigates the multidimensional poverty index (MPI) level and vulnerability to poverty in Pakistan. This study explores MPI province-wise. The MPI consists of three equally weighted dimensions: schooling, health well-being and living standards. This investigation uses a systematic random sampling approach to gather the data from householders from 2003 to 2018. The empirical result demonstrates that 24% of the population was multidimensionally poor in 2007, 20.2% in 2011, 18% in 2014 and 16.4% in 2018, respectively. It identified major determinants of poverty as children mortality and school attendance, cooking fuel and nutrition.